HUBUNGAN TINGKAT STRES DAN POLA MAKAN DENGAN KEJADIAN DIABETES MELLITUS PADA USIA DEWASA SAAT PANDEMI COVID-19 DI PUSKESMAS JATIASIH - Niken Dwi Permata Sari (2022)
Diabetes mellitus is a non-communicable disease and is a chronic disease that is a problem in the world because the incidence continues to increase every year. During the COVID-19 pandemic, there are changes in all aspects of life such as stress and changes in poor diet which are risk factors for diabetes mellitus. The purpose of this study was to determine the relationship between stress levels and diet with the incidence of diabetes mellitus in adults during the COVID-19 pandemic at the Jatiasih Public Health Center. This study uses a cross sectional design, with a sampling technique that is purposive sampling with a total of 189 respondents. The results of the study using the Chi-Square test showed that there was a significant relationship between stress levels and the incidence of diabetes mellitus (p value = 0.000 ≥ 0.05); and a significant relationship between diet and the incidence of diabetes mellitus (p value = 0.041 ≥ 0.05). This research can be used as a source of information for the community in preventing diabetes mellitus, for health workers to provide nursing care and further researchers can use it as a research reference with different risk factors.